Distribusi Nepenthes spp. di Hutan Kalampangan - Lasmitha Dewi; Agus Haryono; Yohanes E. Gunawan (Journal of Environment and Management, 2020)
Kalampangan peat swamp forests in Central Kalimantan is home for Nepenthes spp. However, the number of Nephentes has been reduced due to massive forest fires and land conversion for housing and agricultural purposes. Nepenthes is a unique plant with ability to prey insects, hence often referred to as 'insectivorous plant'. This study investigates the distribution of Nepenthes spp. in Kalampangan forest through ground check and qualitative descriptive approach. A total of six observation plots measuring of 2m x 2m were used purposively. The results show there are four Nepenthes species found, namely Nepenthes gracilis, Nepenthes mirabilis, Nepenthes gracilis cortis, and Nepenthes ampularia. The highest Morisita index is 1.06 while the lowest one is 1.01.